Evaluation of the effects of Cyclotrichium niveum on brain acetylcholinesterase activity and oxidative stress in male rats orally exposed to lead acetate - Sahin, Zafer; Ozkaya, Ahmet; Uckun, Mirac; Yologlu, Ertan; Kuzu, Muslum; Comakli, Veysel; Demirdag, Ramazan; Tel, Ahmet Zafer; Aymelek, Fatih; Yologlu, Semra (Cellular and Molecular Biology, 2019)
Cyclotrichium niveum is an endemic plant for Turkey and it appears to have in vitro antioxidant and acetylcholinesterase inhibition properties. To the best of our knowledge, there has been no study on the in vivo effects of this plant. Therefore, the purpose of this study was to evaluate the effects of C. niveum on lead (Pb)-acetate-induced potential alterations in brain acetylcholinesterase activity, as well as oxidative stress in male rats. The rats were randomly assigned to control, Pb-acetate, C. niveum and Pb-acetate+ C. niveum groups. Pb-acetate was provided in drinking water (500 ppm), and C. niveum was administered via orogastric gavage (4 ml/kg) for 30 days. The acetylcholinesterase activity in the brain significantly decreased only in the Pb-acetate group. The malondialdehyde level significantly increased, and the reduced glutathione activity decreased in the Pb-acetate group. The reduced glutathione and glutathione-S-transferase activities of the C. niveum group were higher than the control group. No Pb was detected on a ppb level in the brain tissue of the control and C. niveum groups, while it was detected in the brains of the rats in the Pb-acetate and Pb-acetate+ C. niveum groups (185+8.98 ppb and 206+56.65 ppb, respectively). The data collected in this study suggested that C. niveum may reduce inhibition of brain AChE activity and oxidative stress against Pb-acetate-induced alterations in the brain of male rats.